A Profile and Index of the CMA Examination. - Harris, John K.; Krogstad, Jack L. (The Accounting Review, 1976)
Abstract The purpose of this article is to provide a content profile and a question index of the Certified Management Accountant (CMA) examination. A content profile of the first four CMA examinations 1972-1975 is presented in the article. This profile is broken down three ways, by subject area, by topic within managerial accounting, the subject area being given the most coverage and by topic within financial reporting, the subject area being given the second-most coverage. The ten subject areas in the profile were identified by integrating typical business administration curriculum formats and course descriptions with the reading list and topical coverage outline distributed by the Institute of Management Accounting. Questions are classified into subject areas and into specific managerial accounting and financial reporting topics on the basis of their content and context and the degree of sophistication indicated by the unofficial answers. Percentages in the profile reveal the average relative emphasis given to the subject areas and topics. Calculations are based on the suggested maximum number of minutes allotted to questions according to the examination instructions. Optional questions involving two or more subject areas are assumed to be selected with equal frequency in each subject area.